THE ARTISTIC DEPICTION OF THE "AMERICAN DREAM" CONCEPT IN 20TH-CENTURY AMERICAN LITERATURE (BASED ON F. SCOTT FITZGERALD’S THE GREAT GATSBY) (Web of Teachers: Inderscience Research, 2025)
This article explores the artistic depiction of the concept of the "American Dream" in 20th-century American literature, with a particular focus on F. Scott Fitzgerald’s novel The Great Gatsby. The study examines how Fitzgerald portrays the ideals of success, wealth, and social mobility, as well as the disillusionment associated with the American Dream. Through an analysis of characters, symbolism, and themes, the article highlights the novel’s critique of the materialistic and morally decaying society of the Jazz Age.